Konsep Kepemimpinan Berbasis Budaya Islam Jawa - Mulyono, Mulyono (el Harakah: Jurnal Budaya Islam, 2009)
Leadership concept based on Javanese-Islamic culture, one of them stem from Wali Songo representing leadership concept having integrity in character such as the king title of Demak: Sayyidin Panata Gama, Senapati Ing Ngalogo, Khalifatullah Fil-Ardh (Most powerful in ruling the religion, commander in battlefield, the leader on earth). The concept of leadership having integrity for Javanese society represents a solid figure in religion, as a moslem scholar, war lord and king as well. The richness of Javanese cultures have leadership values represented in those criteria through brief expression which is full of meaning. In democratic era  and local autonomy in this time, this concept of leadership based on the values of Javanese culture is significant to study as a means to accomodate dynamics of plural society of  Nusantara, so that it has bargaining position of leadership in modern Indonesia. Konsep kepemimpinan berdasarkan budaya Jawa-Islam, salah satunya berasal dari Wali Songo yang mewakili konsep kepemimpinan yang memiliki integritas dalam karakter seperti gelar raja Demak: Sayyidin Panata Gama, Senapati Ing Ngalogo, Khalifatullah Fil-Ardh (Paling berkuasa dalam memerintah agama, komandan di medan perang, pemimpin di bumi). Konsep kepemimpinan yang memiliki integritas untuk masyarakat Jawa mewakili sosok yang solid dalam agama, sebagai seorang ulama, raja dan pimpinan perang juga. Kekayaan budaya Jawa memiliki nilai-nilai kepemimpinan yang diwakili dalam kriteria tersebut melalui ekspresi singkat yang penuh makna. Dalam era demokrasi dan otonomi daerah saat ini, konsep kepemimpinan yang didasarkan pada nilai-nilai budaya Jawa signifikan untuk dipelajari sebagai sarana untuk mengakomodir dinamika masyarakat plural Nusantara, sehingga memiliki posisi tawar kepemimpinan Indonesia modern.